HUBUNGAN KADARZI (KELUARGA SADAR GIZI) DENGAN KEJADIAN STUNTING PADA BALITA USIA 24-59 BULAN - Nur Ayun R. Yusuf; Cindy Puspita Sari Haji Jafar; Felia Pandeirot (PT.Mantaya Idea Batara, 2025)
Stunting is a condition in which toddlers have a height or length below the standard for their age. Stunting in toddlers is a chronic nutritional problem, and one of the reasons for the high prevalence of stunting is the lack of KADARZI (nutritionally aware families) behaviors. This study aims to determine the relationship between KADARZI behaviors and the incidence of stunting among toddlers aged 24-59 months in the working area of Telaga Jaya Health Center. This research is a quantitative study with an analytic survey design using a crosssectional approach. The population consists of mothers and toddlers aged 24-59 months in Telaga Jaya Health Center's working area, with 596 toddlers. The sampling technique used is stratified random sampling, with a total sample size of 120 respondents. Data analysis was performed using the Chi-Square test with a questionnaire as the instrument. The study results showed a significant P-value = 0.000 (Asymp. Sig 2-tailed) with ? = 0.05. The conclusion is that there is a relationship between KADARZI behaviors and the incidence of stunting among toddlers aged 24-59 months in the working area of Telaga Jaya Health Center. This study is expected to provide input or serve as a reference in educating families about the importance of KADARZI behaviors to prevent toddler stunting